A Collaborative solar energy platform - Osunga, Alex; Omar, Zishan; Gitau, Christine; Gitau, Kimani; Shibwabo, Bernard (Strathmore University, 2018)
Energy efficiency awareness is one of the most important steps to achieving the final goal of having a sustainable environment in the country. Together with a good energy policy and regulations, this goal can be achieved as it will help consumers make more rational decisions when it comes to new technology. The main problem nowadays is the lack of awareness and strict energy policies which then gives a channel for the counterfeit products to be shipped in and sold out at low prices. This eventually leads to a very high demand in power and later a struggling economy. The current measures put in place are not vibrant and have not gotten to a large number of people. The government regulations on the other hand are not strict and this causes the inefficient appliances to find their way into the country. The proposed project aims to improve the current status by reaching out to as many people as possible and educate them on the importance of a high initial cost which eventually leads to more savings. It also aims at building a platform where customers can verify that their appliances are energy efficient. In order to have built this platform analysis have been done through research and meeting stakeholders who have provide first-hand information in order to formulate the platform. The information gathered have been used to design a platform that meets the challenges faced in renewable energy.
2018 Conference paper. Theme (Renewable Energy and Energy Efficiency)
Keywords: Renewable energy.; Sustainable environment; Technology; Power supply